Using focus groups data to finalize the Archetypes: Substantiation of Home Occupant Archetypes with the Use of Generative Techniques: Analysis and Results of Focus Groups - SANCHEZ, Marco Antonio ORTIZ; Kim, Dong Hyun; Bluyssen, Philomena M. (A+BE | Architecture and the Built Environment, 2019)
A previous study clustered home occupants into archetypes with a questionnaire. This study uses qualitative methods to strengthen those previously-found archetypes with data pertaining to the participants’ home experiences. Focus groups were carried out where generative activities were conducted involving the generation of collages. The first activity dealt with the expression of ‘meaning of energy use at home’ and the second one with the ‘ideal home experience’. Analyses were done with content and thematic analysis. Codes were drawn from the data and were assimilated through an affinity diagram. The diagram produced two categories: building themes and human themes, along with five sub-categories (home, financial, energy, psychological, and behavioural aspects). The outcome shows that each archetype expresses needs and meanings of an ideal home experience and energy use differently from each other. The results provide evidence that generative techniques can be used in energy research. In this case, to validate and substantiate the quantitative archetypes previously produced with a questionnaire. Interpretive knowledge in energy research allows for a better understanding of occupants’ differing behavioural patterns in regards to energy use and comfort. It allows customizing interventions to the archetypes’ specific needs to decrease energy consumption while maintaining comfort.